2018
DOI: 10.1051/epjconf/201818002063
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional quantitative visualization of isolator shock trains by rainbow schlieren deflectometry

Abstract: Abstract. The rainbow schlieren deflectometry is effective in studying quantitatively the density fields in shock-containing free jets at high precision and high spatial resolution. However, there has been no practical application of rainbow schlieren deflectometry for shock trains in a confined duct. Therefore, in the present study, the rainbow schlieren deflectometry is applied to the flow field including a shock train in a constantarea duct where just upstream of the shock train the freestream Mach number i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…4. In the previous preliminary experiment with the rainbow filter of 1.4mm wide [29,30], it was found that the deflection angle of light ray after passing through the region with a strong density gradient inside a shock train exceeds the upper limit of the rainbow filter. Therefore, a new rainbow filter with a 2.5mm wide strip and continuous hue variation from Hue = 0 to 350 deg was fabricated in the present study.…”
Section: Rainbow Schlieren Optical Systemmentioning
confidence: 95%
See 1 more Smart Citation
“…4. In the previous preliminary experiment with the rainbow filter of 1.4mm wide [29,30], it was found that the deflection angle of light ray after passing through the region with a strong density gradient inside a shock train exceeds the upper limit of the rainbow filter. Therefore, a new rainbow filter with a 2.5mm wide strip and continuous hue variation from Hue = 0 to 350 deg was fabricated in the present study.…”
Section: Rainbow Schlieren Optical Systemmentioning
confidence: 95%
“…with D ≡ 1 + 2 (γ − 1)M 2 1∞ [30]. Note that ( 10) and ( 11) can be also used for laminar boundary layer if the velocity profiles of the laminar boundary layers are assumed in (12).…”
Section: Flow Properties Just Upstream Of Shock Trainmentioning
confidence: 99%